Character and characterization in kazuo ishiguro’s crooner - Widiasmoro, Yohanes Mahatmo Suryo (LPPM Universitas Mercu Buana Yogyakarta, 2023)
This study focuses on the character and characterization of Janeck and Tony Gardner in Kazuo Ishiguro’s short story “Crooner”. The short story is featured as the first short story in Ishiguro’s short story collection titled Nocturnes: Five Stories of Music and Nightfall. “Crooner” is a story of a “gypsy” or freelance musician named Janeck who helps an iconic American singer named Tony Gardner to serenade his wife. The story takes place in Venice, Italy. The data are gathered by conducting library research. The data are the short story “Crooner,” related theories and previous studies taken from books and journals. The data are analyzed using the theory of character, and the theory of characterization. The result of this study shows the characters of Janeck in the story are friendly, hospitable, enthusiastic, curious, and professional. Meanwhile, the characters of Tony Gardner in the story are kind, assertive, romantic, and realistic or sensible